Comparison of the sugar and organic acid components of seventeen table grape varieties produced in Ankara (Türkiye): a study over two consecutive seasons - Kunter, Birhan; Unal, Osman Batur; Keskin, Sıddık; Hatterman-Valenti, Harlene; Kaya, Ozkan (Frontiers in Plant Science, 2024)
Sugars and organic acids have a significant impact not only on taste balance and sensory acceptance by consumers but also play a crucial role in the chemical equilibrium of grape juices and wines. Therefore, this study aimed to quantify the content and composition of sugars and organic acids in a total of 17 grape varieties over two consecutive years using high-performance liquid chromatography. It was observed that the variability in all the parameters studied was strongly influenced by both the grape cultivars and the specific years. In grape berries, the primary sugars identified were fructose and glucose, ranging from 6.50 to 11.10 g/L and 5.83 to 12.12 g/L, respectively, over the two years. However, sucrose was not detected in all the grape varieties. The highest titratable acidity (TA) was found in Tekirdağ Çekirdeksizi (TeCe), while the lowest was detected in Victoria (Vi) for the two respective years. Soluble solids (TSS) reached its peak in Horoz Karası (HoKA), whereas it hit the lowest point in Big Perlon (BiPe).The tartaric acid content in the grape berries, ranging from 1.48 to 10.33 g/L for the two years, exhibited similar characteristics to malic acid, which ranged from 1.09 to 9.62 g/L and 1.03 to 9.68 g/L for the two respective years. The succinic, malic, tartaric, citric, and oxalic acid content was notably higher in the Kyoho (Ky) variety compared to the other varieties. When examining the dendrogram of organic acid and sugar contents for similarities, it was evident that there was a high degree of similarity among 16 out of 17 grape varieties, except for Alphonse Lavallée (AlLa) and Horoz Karası (HoKa). The similarity levels among the varieties ranged from 99.49% to 72.36%. The highest similarity, 99.49%, was found between the Alphonse Lavallée (AlLa) and Barış (Ba) varieties. On the other hand, the lowest similarity was observed between the Alphonse Lavallée (AlLa), Horoz Karası (HoKa), and Kyoho (Ky) varieties. In summary, this research underscores that certain table grape varieties grown in Ankara exhibit significant variations in valuable organic acids and sugars, which are associated with potential health benefits when considering human consumption.